Local Portraiture : Through the Lens of the 19th Century Iranian Photographers - Perez González, Carmen, 1969- (Book collections on Project MUSE., 2012)
Photography is clearly not a mirror of daily life: that images are constructions is especially obvious in19th-century studio portrait photography. This book explores how indigenous Iranian photographers constructed their own realities in contrast to how foreign photographers constructed Iranians' realities. Through an in-depth comparative visual analysis of 19th-century Iranian portrait photography and Persian painting, the author arrives at the insight that aesthetic preferences correlate with socio-cultural habits and practices in writing, reading and looking. Subsequently, she advocates for a place in a global history of photography for those unknown, local photo histories (such as the Iranian one) and for the indigenous photographers who produced them.